How digital technology affects working conditions in globally fragmented production chains: Evidence from Europe - Aleksandra Parteka; Joanna Wolszczak-Derlacz; Dagmara Nikulin (Gdańsk University of Technology, Faculty of Management and Economics, 2021)
This paper uses a sample of over 9.5 million workers from 22 European countries to study the intertwined effects of digital technology and cross-border production links on workers' wellbeing. We compare the social effects of technological change exhibited by three types of innovation: computerisation (software), automation (robots) and artificial intelligence (AI). To fully quantify work-related wellbeing, we propose a new methodology that corrects the information on remuneration by reference to such non-monetary factors as the work environment (physical and social), career development prospects, or work intensity. We show that workers' wellbeing depends on the type of technological exposure. Employees in occupations with high software or robots content face worse working conditions than those exposed to AI. The impact of digitalisation on working conditions depends on participation in global production. To demonstrate this, we estimate a set of augmented models for determination of working conditions, interacting technological factors with Global Value Chain participation. GVC intensification is accompanied by deteriorating working conditions - but only in occupations exposed to robots or software, not in AI-intensive jobs. In other words, we find that AI technologies differ from previous waves of technological progress - also in their impact on workers' wellbeing within global production structures.
Keywords: F1; F6; J8; O3; 330; digital technologies; working conditions; GVC; Global Value Chains; artificial intelligence; AI